Experiences and needs of front-line nurses during the COVID-19 pandemic: A systematic review and qualitative meta-synthesis - Ding, Shenglan; Deng, Shuhua; Zhang, Yilan; Wang, Qingxia; Liu, Zhiping; Huang, Jing; Yang, Xiaorong (Frontiers in Public Health, 2022)
Background: Front-line nurses have played a critical role during the coronavirus disease 2019 (COVID-19) pandemic. A number of qualitative studies reported front-line nurses’ experiences and needs in caring for COVID-19 patients. However, the application of evidence from a single qualitative study to guide clinical practice has limitations. This study aimed to explore front-line nurses’ experiences and needs during the COVID-19 pandemic through a qualitative meta-synthesis. Methods: Seven databases were searched from 1 December 2019 to 20 January 2022, including PubMed, Web of Science, Cochrane COVID-19 study register, CINAHL, PsycINFO, MedRxiv and bioRxiv. The quality of included studies was appraised using the Critical Appraisal Skills Program (CASP) qualitative research appraisal tool. Meta-synthesis was used to synthesize the data from included studies. Results: A total of 70 studies were included and five synthesized findings were developed: (1) Although nurses actively devoted themselves to fighting against COVID-19 considering their professional responsibility and historical previous experience with mankind, they were not invulnerable; (2) There were various difficulties and challenges in caring for COVID-19 patients including fear related to providing patients with care, shortage of protective equipment and manpower, and negative attitude of family members; (3) Facing difficulties and challenges, nurses could only partly cope by using mixed means to overcome those including media, learning, gaining skills, responding together, and organizational assistance; (4) To better respond to the COVID-19 pandemic, nurses' needs should be paid attention to. Counselling, training, information, resources, and investment are pivotal; (5) Despite the hardships, nurses became stronger and gained gratitude, positivity, mental peace, and confidence. Conclusions: This study reveals that the psychological experiences of front-line nurses were varied and they faced a variety of challenges. Although nurses had some coping strategies, they still needed multifaceted support to meet the challenges.